VD_FINDINFO HC / 2009 / 50 vom 14. Dezember 2007 - VD Tribunal cantonal (2007)
JUGEMENT PAR DÉFAUT, COMPARUTION PERSONNELLE | 305 al. 2 CPC, 312 CPC, 313 CPC, 444 al. 1 ch. 3 CPC, 465 al. 1 CPC, 46 LJT